Seroprevalence of Neospora caninum in dairy cows in Belgrade city area, Serbia - CVETOJEVIC, Đ.; MILICEVIC, V.; KURELJUSIC, B.; SAVIC, B. (Journal of the Hellenic Veterinary Medical Society, 2018)
The protozoan parasite Neospora caninum is one of the most important abortifacient pathogen in cattle. Serological investigations are often used in order to estimate seroprevalence in herds. Aims of our study were to determine the seroprevalence among aborting and non-aborting dairy cattle in Belgrade city area as well as epidemiological factors that are important for N. caninum infection. Using commercial ELISA kit, we examined 188 sera. Out of 188, 142 samples originated from pregnant (non-aborting) cows from five farms, while 46 were from cows who had aborted. Overall seroprevalence was 25% (48/188). Seroprevalence was significantly higher (p≤0.05) in aborting than in non-aborting group of cows (37% and 21.1% respectively). At least one positive sample was detected on four (80%) out of five examined farms while seroprevalence among farms varied from 0 to 43.5%. On all examined farms crucial epizootiological factors (presence of dogs and low biosecurity measures) that favor the maintenance and spreading of the infection were identified. Our study revealed the presence of N. caninum antibodies in population of dairy cows in Belgrade city area. Infection is established in enzootic pattern on examined farms and high seroprevalence among aborting cows suggests that N. caninum could be important abortifacient pathogen.